The association between number and ages of children and the physical activity of mothers: Cross-sectional analyses from the Southampton Women’s Survey - Simpson, Rachel F.; Hesketh, Kathryn R.; Crozier, Sarah R.; Baird, Janis; Cooper, Cyrus; Godfrey, Keith M.; Harvey, Nicholas C.; Westgate, Kate; Inskip, Hazel M.; van Sluijs, Esther M. F. (PLOS ONE, 2022)
Background Physical activity (PA) has many health benefits, but motherhood is often associated with reduced PA. Considering that ages and number of children may be associated with maternal PA, and that PA patterns may change as children transition to formal schooling, we aimed to investigate the associations between ages and number of children and device-measured maternal PA. Methods Cross-sectional analyses were conducted using data from 848 mothers from the Southampton Women’s Survey at two different timepoints. Two-level random intercept linear models were used to investigate associations between ages (≤4y(ears) (“younger”), school-aged, both age groups) and number (1, 2, ≥3) of children, and their interaction, and accelerometer-assessed minutes of maternal moderate or vigorous PA (log-transformed MVPA) and light, moderate or vigorous PA (LMVPA). Results Women with any school-aged children engaged in more MVPA than those with only ≤4y (e.g. % difference in minutes of MVPA [95% confidence interval]: 46.9% [22.0;77.0] for mothers with only school-aged vs only ≤4y). Mothers with multiple children did less MVPA than those with 1 child (e.g. 12.5% [-1.1;24.3] less MVPA for those with 2 children). For mothers with multiple children, those with any school-aged children did less LMVPA than those with only ≤4y (e.g. amongst mothers with 2 children, those with only school-aged children did 34.0 [3.9;64.1] mins/day less LMVPA). For mothers with any ≤4y, those with more children did more LMVPA (e.g. amongst mothers with only ≤4y, those with 2 children did 42.6 [16.4;68.8] mins/day more LMVPA than those with 1 child). Conclusions Mothers with multiple children and only children aged ≤4y did less MVPA. Considering that many of these women also did more LMVPA than mothers with fewer or older children, interventions and policies are needed to increase their opportunities for higher intensity PA to maximise health benefits. Trial registration ClinicalTrials.gov Identifier: NCT04715945.